Англо-русский фразеологический словарь: около 25000 фразеол. единиц / сост. А. В. Кунин - Кунин Александр Владимирович (ГИС, 1956)
Экземпляры: ИН (20111026) / Инвентарный номер: 205831 / Цена: 21.30 / Сис.шифр: 81.432.1-4 / Авт.знак: К 91 / ГРНТИ: 16 / ББК: 81.432.1-4